A zonal grid method for incompressible two-phase flows. (15th February 2019) - Dabonneville, F.; Hecht, N.; Reveillon, J.; Pinon, G.; Demoulin, F.X.
Highlights: A new zonal grid based numerical method applicable to two-phase flows. Strong reduction of the computational time for flows with high speed gradients. Possibility to use multi-models, multi-solvers and multi- timesteps. successfully applied on a full 3D liquid jet atomization configuration. Abstract: We present a zonal grid based numerical method applicable to two-phase flows. The method is aimed at reducing the computational costs for interfacial flows involving local high velocity gradients such as those encountered in atomization systems. The objective is to fully resolve the primary atomization region while at the same time limiting the number of grid points in secondary or dispersed zones where a very fine grid is not required, along with the ability to use a local zone based time step. Calculations of a rising bubble and liquid jet atomization configurations were performed on a coarse grid with a fine zone superimposed on small domains with the strongest gradient. The results show good agreement with simulations carried out with a complete refined mesh with only a fraction of the CPU time. The results indicate that the two-phase zonal grid model approach introduced here has the potential to provide an accurate and cost-effective approach for modeling two-phase flow problems that have multiple temporal and spatial scales.